The Influence of Green Accounting on Stock Prices With Financial Performance - Adam Fawwaz Ar-Rasyid; Aranta Prista Dilasari; Achmad Farid Dedyansyah; Agustinus Salukh (Journal of Economy, Accounting and Management Science (JEAMS), 2025)
This study aims to analyze the effect of green accounting on stock price growth with financial performance as a moderating variable in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The data used are annual financial reports and year-end closing stock prices. The data analysis technique uses multiple regression and Moderated Regression Analysis (MRA). The results of the study show that green accounting has a significant but negative effect on stock price growth. Financial performance does not have a significant direct effect on stock price growth, but significantly moderates the relationship between green accounting and stock price growth. This finding supports the Signaling theory, which states that good financial performance strengthens investor confidence in the effective implementation of green accounting. Therefore, companies that are able to maintain financial stability can improve market perceptions of the sustainability practices they carry out.